Role of magnifying endoscopy with narrow‐band imaging in the diagnosis of noninvasive gastric neoplasia. Issue 4 (26th February 2021) - Tanaka, Keisuke; Maekawa, Shinya; Yoshida, Takashi; Yamaguchi, Tatsuya; Takano, Shinichi; Matsuda, Shuya; Hayakawa, Hiroshi; Ishida, Yasuaki; Muraoka, Masaru; Kawakami, Satoshi; Fukasawa, Yoshimitsu; Kuno, Toru; et al.
Abstract: Background and Aim: There are no globally approved, distinguishing criteria enabling the classification of gastric adenomas and intramucosal carcinomas for differential diagnosis of noninvasive neoplasia (NIN). Methods: Next‐generation sequencing of 50 cancer‐related genes was undertaken on 68 pathologically diagnosed microdissected gastric neoplasms (25 adenomas, 27 intramucosal carcinomas, and 16 submucosal carcinomas) obtained during endoscopic submucosal dissection. Findings from magnifying endoscopy with narrow‐band imaging (M‐NBI) of 52 NINs (the 25 adenomas and 27 intramucosal carcinomas) were compared with these data. Results: Among all 68 neoplasms, the most frequently mutated genes were APC (76% in adenoma, 11.1% in intramucosal carcinoma, and 0% in submucosal carcinoma; P  < 0.001) and TP53 in intramucosal and submucosal carcinomas (8% in adenoma, 48.1% in intramucosal carcinoma, and 75% in submucosal carcinoma; P  < 0.001). Dividing the NIN neoplasms into five groups according to their mutational status (A1: APC mutation, A2: APC  + α mutation, B: APC  +  TP53 mutation, C: TP53 mutation, D: no mutation in either APC or TP53 ) resulted in almost identical diagnoses by pathology and M‐NBI for groups A1 (12/13, 92%), C (12/13, 92%), and D (16/17, 94%) but not for groups A2 (3/7, 43%) or B (0/2, 0%). This finding implies that NINs with the APC  + α mutation have carcinoma‐like endoscopic features despite most being judged as adenomas by pathology. Conclusion: A diagnosis of NINs by pathology or M‐NBI in the subset of gastric tumors classified by cancer‐related mutations is not completely identical, suggesting the possible additional role of M‐NBI in diagnosing NINs. Further studies are needed to confirm this. Abstract : Through a semiquantitative analysis of cancer‐related genes, it was found that noninvasive intraepithelial neoplasia (NIN) diagnosed as adenoma by both pathology and magnifying endoscopy with narrow‐band imaging (M‐NBI) had a profile of a single APC mutation, while NINs diagnosed as intramucosal carcinoma by both methods had a profile of TP53 mutation in most of the cases. On the other hand, some NINs were diagnosed as adenomas by pathology but were diagnosed as intramucosal carcinomas by M‐NBI, and such NINs with discrepant diagnoses had a characteristic profile of APC plus other mutation(s), suggesting that the M‐NBI finding reflects biological change and might be important for the diagnosis of NINs.